Functional annotation and investigation of the 10q24.33 melanoma risk locus identifies a common variant that influences transcriptional regulation of OBFC1. Issue 6 (4th October 2021) - Cardinale, Antonella; Cantalupo, Sueva; Lasorsa, Vito Alessandro; Montella, Annalaura; Cimmino, Flora; Succoio, Mariangela; Vermeulen, Michiel; Baltissen, Marijke P; Esposito, Matteo; Avitabile, Marianna; Formicola, Daniela; Testori, Alessandro; et al.
Abstract: The 10q24.33 locus is known to be associated with susceptibility to cutaneous malignant melanoma (CMM), but the mechanisms underlying this association have been not extensively investigated. We carried out an integrative genomic analysis of 10q24.33 using epigenomic annotations and in vitro reporter gene assays to identify regulatory variants. We found two putative functional single nucleotide polymorphisms (SNPs) in an enhancer and in the promoter of OBFC1, respectively, in neural crest and CMM cells, one, rs2995264, altering enhancer activity. The minor allele G of rs2995264 correlated with lower OBFC1 expression in 470 CMM tumors and was confirmed to increase the CMM risk in a cohort of 484 CMM cases and 1801 controls of Italian origin. Hi-C and chromosome conformation capture (3C) experiments showed the interaction between the enhancer-SNP region and the promoter of OBFC1 and an isogenic model characterized by CRISPR-Cas9 deletion of the enhancer-SNP region confirmed the potential regulatory effect of rs2995264 on OBFC1 transcription. Moreover, the presence of G-rs2995264 risk allele reduced the binding affinity of the transcription factor MEOX2 . Biologic investigations showed significant cell viability upon depletion of OBFC1, specifically in CMM cells that were homozygous for the protective allele. Clinically, high levels of OBFC1 expression associated with histologically favorable CMM tumors. Finally, preliminary results suggested the potential effect of decreased OBFC1 expression on telomerase activity in tumorigenic conditions. Our results support the hypothesis that reduced expression of OBFC1 gene through functional heritable DNA variation can contribute to malignant transformation of normal melanocytes.